Di Balik Kinerja Pegawai: Peran Tersembunyi Kepemimpinan dan Budaya Organisasi - Andi Sopandi; Warman Warman; Mahwiyah Mahwiyah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to examine the role of leadership and organizational culture in shaping employee performance at PT Prima Jaya Makmur using a quantitative associative approach. The population consists of 375 employees, including doctors, midwives, nurses, and non-medical staff, with a sample of 128 respondents determined through proportional random sampling using the Slovin formula. Data analysis techniques include instrument testing (validity and reliability) and multiple linear regression analysis. The findings indicate that leadership contributes to improving employee performance through the ability to provide clear direction, foster effective communication, and demonstrate exemplary behavior. Meanwhile, organizational culture plays a more dominant role in shaping work behavior, as the values and norms embedded within the organization encourage consistency, discipline, and employee commitment. Collectively, leadership and organizational culture create a synergy that strengthens employee performance more optimally.